Financial Risk Management Via Econometric Model On Saigon Beer Western Jsc. Stock Price – A Case In F&B Industry In Vietnam - Manh, Pham Tien; Huong, Tran Thi Thu (The journal of contemporary issues in business and government, 2021)
GDP growth in Vietnam, controlled inflation and population growth around 1% (2018) are positive figures to encourage business operation of Saigon Beer Western JSC. (WSB). Fluctuation of stock price in F&B firms such as WSB in Vietnam will reflect the business health of F&B industry and consuming economy. Good business management requires us to consider the impacts of multi macro factors on stock price, and it contributes to promoting business plan and economic policies for economic growth and stabilizing macroeconomic factors. By data collection method through statistics, analysis, synthesis, comparison, quantitative analysis to generate qualitative comments and discussion; using econometric method to perform regression equation and evaluate quantitative results, the article analyzed and evaluated the impacts of six (6) macroeconomic factors on stock price of a joint stock F&B company, Saigon Beer Western JSC (WSB) in Vietnam in the period of 2014-2019, both positive and negative sides. The results of quantitative research, in a seven factor model, show that the decrease in CPI and increase in lending rate has a significant effect on decreasing WSB stock price with the highest impact coefficient, the second is increasing the risk free rate. This research finding and recommended policy also can be used as reference in policy for commercial bank system in many developing countries.